Mô hình chuỗi trung gian nối tiếp về tài sản thương hiệu điểm đến - Lê Nhật , Hạnh; Trần Thị Kim , Phương; Nguyễn Đông , Phong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
From a consumer-brand relationship perspective, this study proposes a serial multiple mediation model to explore the pathways (e.g., cognitive, affective, and hybrid) to increase destination brand equity. A paper-based survey was used to collect data from 749 domestic tourists visiting Thua Thien Hue, Da Nang, and Hoi An in Vietnam. The research model is evaluated through CB-SEM. The results confirmed three pathways among antecedents (e.g., self-congruity) and components of destination brand equity. These findings provide practical implications for destination managers.
Keywords: Destination Brand Equity; Self-congruity; Serial Multiple Mediation model; Vietnam